Interaction of Saturn's Hexagon With Convective Storms. Issue 8 (26th April 2021) - Sánchez‐Lavega, A.; García‐Melendo, E.; del Río‐Gaztelurrutia, T.; Hueso, R.; Simon, A.; Wong, M. H.; Ahrens‐Velásquez, K.; Soria, M.; Barry, T.; Go, C.; Foster, C.
Abstract: In March 2020, a convective storm erupted at planetographic latitude 76°N in the southern flank of Saturn's long‐lived hexagonal wave. The storm reached a zonal size of 4, 500 km and developed a tail extending zonally 33, 000 km. Two new short‐lived storms erupted in May in the hexagon edge. These storms formed after the convective storms that took place in 2018 in nearby latitudes. There were no noticeable changes in the zonal profile of Saturn's polar winds in 2018–2020. Measurements of the longitude position of the vertices of the hexagon throughout this period yield a value for its period of rotation equal to that of System III of radio rotation measured at the time of Voyagers. We report changes in the hexagon clouds related to the activity of the storms. Our study reinforces the idea that Saturn's hexagon is a well‐rooted structure with a possible direct relationship with the bulk rotation of the planet. Plain Language Summary: Convective storms of zonal extents greater than 4, 000 km are rare in Saturn's atmosphere. They occur every few years, and exceptionally (perhaps once every 20–30 years) they reach 10, 000 km and become a Great White Spot that expands along an entire latitudinal band of the planet. In 2018, multiple eruptions of medium‐sized storms occurred close to the North Polar Region. After a period of calm throughout 2019, new eruptions took place in 2020 at 76°N latitude on the border of the hexagon wave, the closest to the pole ever observed. These storms changed the morphology of the clouds in the region, but the hexagon itself was not affected in its motion or dynamics, with no change in the zonal winds. This, together with its longevity, indicates that the hexagon is a robust meteorological formation. Its rotation period in these years remained that of the System III radio rotation measured by the Voyager spacecraft, reinforcing the idea of its possible direct relationship with the bulk rotation of the planet. Key Points: Following an outbreak of polar storms in 2018, we observed in March–May 2020 a new episode of storms south of Saturn's hexagonal wave The storms did not produce a noticeable change in the zonal wind profile in the polar area The hexagon shape was perturbed after the storms but the wave suffered no change in its rotation period matching that of System III